Death in the intensive therapy unit: nursing perceptions - Maria Aliny Pinto da Cunha, Elizângela Pereira da Silva Santos, Maria Tamires Alves Ferreira, Luciana Stanford Baldoino, Ana Maria Santos da Costa, Aclênia Maria Nascimento Ribeiro (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v9i0.9699